Thymic stromal lymphopoietin (TSLP) and Toluene-diisocyanate-induced airway inflammation: Alleviation by TSLP neutralizing antibody. (15th December 2019) - Yu, Gongchang; Zhang, Yu; Wang, Xiaoqun; Sai, Linlin; Bo, Cunxiang; Yeo, Abrey J.; Lavin, Martin F.; Peng, Cheng; Jia, Qiang; Shao, Hua
Highlights: Toluene-diisocyanate (TDI) is the most common cause of occupational asthma. Th1/Th2 cells responses and Th17/Treg cells imbalance are involved in the important pathological mechanisms of asthma. Thymic stromal lymphopoietin (TSLP) plays an important role in the development of TDI-induced asthma. TSLP neutralizing antibody (TSLP-Ab) can effectively alleviate airway inflammation of TDI-induced asthma. Abstract: Toluene-diisocyanate (TDI) is mainly used in the manufacturing process of polyurethane foams, and is a potent inducer of occupational asthma characterized by airway inflammation and airway hyperreactivity. Thymic stromal lymphopoietin (TSLP) plays an important role in the development of asthma, and correlating with the differentiation of Th2 and Th17 cells. However, the role of TSLP in TDI-induced asthma remains unclear. In this study, 96 TDI-exposed workers as well as a mouse model of TDI-induced asthma were investigated. The air exposure assessment result of TDI in the workplace showed that workers were exposed to inhalation of a very high concentration of TDI, approximately 8 times the recommended level, leading to a decrease in pulmonary function and an increase in inflammatory cells, as well as TSLP and IgE levels in the supernatant of sputum obtained from exposed workers. In order to further investigate the role of TSLP in the pathogenesis of TDI-induced asthma, a mouse model of TDI-induced asthma was also employed. Histopathological analysis of mouse lung and bronchus showed an obvious infiltration of inflammatory cells around the bronchus. The levels of inflammatory cells, IFN-γ, IL-4 and IL-17 in bronchoalveolar lavage fluid (BALF), the expression levels of TSLP protein and ROR-γt and IL-17 mRNA in mouse lung tissues were also significantly increased. However, after treatment with TSLP neutralizing antibody (TSLP-Ab), the degree of pulmonary and bronchial inflammation in mice was significantly alleviated, and the levels of inflammatory cells, IFN-γ, IL-4 and IL-17 in BALF, and the expression levels of ROR-γt and IL-17 mRNA in lung tissue were significantly decreased. Our data shows that TSLP plays an important role in the pathogenesis of TDI-induced asthma, and that TSLP-Ab can effectively alleviate TDI-induced airway inflammation of asthma.